An internal auditor's commitment to independence: influence of role theory and audit-based monitoring mechanisms / Zaini Ahmad - Ahmad, Zaini (2010)
The purpose of this dissertation is to construct and empirically examine a model for an internal auditor's commitment to independence (IACTI) with individual and organizational factors. At the individual level, the relationship between role ambiguity, role conflict and IACTI is examined. At the organizational level, this study examines the relationship between the quality of the external auditor's engagement, the quality of the audit committee composition and IACTI. A hypothesized moderating effect of quality of external auditor's engagement on the relationship between role ambiguity and role conflict was also tested. Data obtained from 101 in-house internal auditors of publiclisted companies in Malaysia were used to test the hypotheses. The model was assessed using hierarchical linear regression and moderated regression analysis. Overall, the results provided significant relationships between role ambiguity, role conflict and quality of audit committee composition on IACTI. Nevertheless, no significant relationship was found between quality of external auditor's engagement and IACTI. In addition, the results did not seem to indicate any support for the moderating effect of the quality of external auditor's engagement in the relationship between role ambiguity and IACTI. In contrast, the moderating effect of the quality of external auditor's engagement was found to be significant in the relationship between role conflict and internal auditor's commitment to independence (IACTI). This study makes several contributions to the literature on internal auditing, management and corporate governance.